1957
DOI: 10.1071/bi9570337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 3-Indolylacetic Acid on the Binding of Pectin Methylesterase to the Cell Walls of Tobacco Pith

Abstract: 3-Indolylacetic acid (IAA) was found to promote the binding of pectin methylesterase (PME) to a cell wall fraction prepared from tobacco pith, the effect being increased by increasing concentration of IAA to a peak of activity, after which inhibition occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1959
1959
1961
1961

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…According to Thornton (1936) the deformation of root hairs, which is believed to be caused by bacterial IAA, is a necessary prelude to infection. However, our present knowledge of the action of IAA on cell walls-which might involve an immobilization of pectin methylesterase (Glasziou, 1957;Fiihraeus & Ljunggren, 1959)-are too vague to permit detailed conclusions about the role of…”
Section: Discussionmentioning
confidence: 99%
“…According to Thornton (1936) the deformation of root hairs, which is believed to be caused by bacterial IAA, is a necessary prelude to infection. However, our present knowledge of the action of IAA on cell walls-which might involve an immobilization of pectin methylesterase (Glasziou, 1957;Fiihraeus & Ljunggren, 1959)-are too vague to permit detailed conclusions about the role of…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of reactions occurring in the initial phase which auxins reportedly affect in a stimulatory manner (3,9,15,19). What is more significant concerning these reactions is that they can occur prior to any determinable growth and once completed will allow elongation to proceed even in the absence of external auxin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were noted when 10 M indole acetic acid (lAA) was added to the roots of white clover and the authors suggested that the increase in PME bound to the plant material was due to the action of lAA. Such an effect of lAA had been reported for tobacco pith by Bryan and Newcomb (1954) and Glasziou (1957).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Reduction of water-holding capacity may make plant tissue more susceptible to attack by bacteria (Fernando and Stevenson, 1952;Gregg, 1952). Glasziou (1957) and Glasziou and Inglis (1958) suggested that binding of PME to cell walls inactivated the enzyme and that enzyme binding prevented de-esterification of pectin, thereby decreasing the amount of calcium bridging. The importance of PME in cell wall plasticity was later questioned by Jansen e^ aJL.…”
Section: Effects Of Combined Nitrogen On Nodulationmentioning
confidence: 99%
See 1 more Smart Citation